Interest Rate Dynamics and Firm Value: A Qualitative Systematic Review of Corporate Performance and Stock Returns - Agus Rohmat Hidayat; Feri Hardiyanto; Rudi Ferdiansah (PT. Publikasiku Academic Solution, 2026)
Exchange rate stability and Bank Indonesia’s monetary policy play a crucial role in maintaining Indonesia’s macroeconomic resilience, particularly amid global uncertainty, inflationary pressure, capital flow volatility, and changes in international monetary policy. Previous studies have discussed exchange rate movements, interest rates, inflation, banking performance, digital finance, and macroeconomic uncertainty, but these discussions remain fragmented across different economic contexts. This research aims to examine the role of exchange rate dynamics and Bank Indonesia’s monetary policy in supporting macroeconomic stability, banking performance, and financial resilience in Indonesia. This research applies a qualitative literature review approach by synthesizing previous studies related to exchange rates, monetary policy, banking, inflation, digital finance, imports, exports, and macroeconomic uncertainty. The analysis focuses on identifying key themes, relationships, and policy implications from relevant academic sources. The findings indicate that exchange rate fluctuations affect export-import activities, inflation, purchasing power, banking performance, and business sustainability. Bank Indonesia’s monetary policy, including interest rate management, liquidity regulation, and digital payment system development, contributes to strengthening economic stability and financial system resilience. Exchange rate stability and adaptive monetary policy are essential for sustaining Indonesia’s economic resilience. Strong coordination between monetary policy, banking regulation, and real-sector strategies is needed to reduce macroeconomic vulnerability.